Protein O‐GlcNAcylation in the heart. (17th June 2021) - Ng, Yann Huey; Okolo, Chidinma A.; Erickson, Jeffrey R.; Baldi, James C.; Jones, Peter P.
Abstract: O‐GlcNAcylation is a ubiquitous post‐translational modification that is extremely labile and plays a significant role in physiology, including the heart. Sustained activation of cardiac O‐GlcNAcylation is frequently associated with alterations in cellular metabolism, leading to detrimental effects on cardiovascular function. This is particularly true during conditions such as diabetes, hypertension, cardiac remodelling, heart failure and arrhythmogenesis. Paradoxically, transient elevation of cardiac protein O‐GlcNAcylation can also exert beneficial effects in the heart. There is compelling evidence to suggest that a complex interaction between O‐GlcNAcylation and phosphorylation also exists in the heart. Beyond direct functional consequences on cardiomyocytes, O‐GlcNAcylation also acts indirectly by altering the function of transcription factors that affect downstream signalling. This review focuses on the potential cardioprotective role of protein O‐GlcNAcylation during ischaemia‐reperfusion injury, the deleterious consequences of chronically elevated O‐GlcNAc levels, the interplay between O‐GlcNAcylation and phosphorylation in the cardiomyocytes and the effects of O‐GlcNAcylation on other major non‐myocyte cell types in the heart.